“That’s the biggest impact!” Pedagogical values of movies in ELT classrooms - Nyak Mutia Ismail (Studies in English Language and Education, 2017)
Since many say watching movies can have a positive effect on language learning outcomes, this research was done to find out which skills movies can contribute most to, whether speaking, listening, reading, writing, vocabulary, grammar or cultural aspects. A qualitative research method was used for this study. This study was done to find out the teachers’ perceptions of using English movies in English Language Teaching (ELT) processes. Teachers from three different levels: primary, secondary, and senior high-school teachers were asked to answer a questionnaire set in accordance with the research topic. Five of them were senior high school teachers, two of them were junior high school teachers, and three of them were elementary school teachers. Creative interviews were also used as an additional data source. The results showed that most of the teachers agreed that movies play their biggest role and considerable advantages in developing cultural aspects and listening skills. Furthermore, some integration is possible between listening and speaking as well as with reading and writing because watching movies works better with integration of skills. Apparently, even though vocabulary can develop with this technique, grammar is not enhanced alone without being accompanied by writing.